(untitled) (Revista Latino-Americana de Enfermagem, 2006)
This study described the daily life of schizophrenia patients after the use of clozapine and group accompaniment from the perspective of family members. The research population consisted of 11 family members who most frequently accompanied 11 schizophrenia patients who participate in the group and use clozapine. With a view to data collection, interviews oriented by a script were held in April 2003, which were taped and fully transcribed afterwards. Results indicated an improvement in patients' symptoms, demonstrated by decreased social isolation, resumption of home/work activities and study as well as by participation in social events. These results point towards the need for a new view on patients who suffer from mental disorder and their family members, with a view to seeking therapeutic attitudes that act in the production of life with a view to a new existential meaning, in the different forms of social contact and sociability.